2021
DOI: 10.3390/su13179707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Air Temperature on School Teachers’ Mood and the Perception of Students’ Behavior

Abstract: This study investigates how temperature, inside and outside the classroom, influence teachers’ mood and mental fatigue as well as the perceived students’ behavior. Two daily random measurements of the temperature inside various classrooms were taken for 7 months. Mood, mental fatigue, and perception of students’ behavior were evaluated for the teachers. Daily external temperature data were obtained from the State Agency of Meteorology. Results showed that indoor temperature, indoor humidity, and the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As discussed below, evidence links extreme indoor temperatures with low student attendance, high teacher absenteeism, poor cognitive performance, and worse learning outcomes (⇡Barbic et al, 2019;⇡Boix-Vilella et al, 2021;⇡Dupont et al, 2023;⇡Simmons et al, 2008;⇡Toftum et al, 2021;⇡Wargocki et al, 2019). Figure 4.3 outlines the impact of climate change on the temperature and resilience of school buildings, as well as the impact of higher indoor temperatures on learning outcomes.…”
Section: The Impact Of Temperature On Learning Outcomesmentioning
confidence: 99%
“…As discussed below, evidence links extreme indoor temperatures with low student attendance, high teacher absenteeism, poor cognitive performance, and worse learning outcomes (⇡Barbic et al, 2019;⇡Boix-Vilella et al, 2021;⇡Dupont et al, 2023;⇡Simmons et al, 2008;⇡Toftum et al, 2021;⇡Wargocki et al, 2019). Figure 4.3 outlines the impact of climate change on the temperature and resilience of school buildings, as well as the impact of higher indoor temperatures on learning outcomes.…”
Section: The Impact Of Temperature On Learning Outcomesmentioning
confidence: 99%
“…Despite this regulation, lighting has a component that directly affects people: color temperature [5]. This is determined from the radiation principle of a black body and can be categorized into two variations: cold light (blue light), which occurs within the 10,000 °K range; and warm light (red light), which occurs from 1000 °K [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In psychological research, researchers have found that temperature can affect people's emotions (Boix-Vilella et al, 2021;Cai et al, 2021). Meteorological psychologists pointed out that temperature affects people's body, spirit, speech and behavior (Dijksterhuis et al, 2005;Kopec, 2018).…”
Section: Introductionmentioning
confidence: 99%